The Diagnostic and Prognostic Value of Plasma Galectin 3 in HFrEF Related to the Etiology of Heart Failure - Lu, Qun; Zhang, Ruo-Chen; Chen, Shu-Ping; Li, Tao; Wang, Ya; Xue, Yan-Bo; Liu, Jing; Han, Xiu; Su, Yi-Dan; Bai, Ling; Du, Xiao-Jun; Ma, Ai-Qun (Frontiers in Cardiovascular Medicine, 2021)
Aim: The aim of the study was to evaluate the diagnostic and prognostic value of plasma galectin 3 (Gal-3) for HF originating from different causes. Methods: We examined the plasma levels and expression of Gal-3 in cardiac tissues in two transgenic (TG) strains of mice with cardiomyocyte-restricted overexpression of either β2- adrenergic receptor (β2- AR TG) or Mammalian sterile 20-like kinase 1 (Mst1-TG) in the present study. Additionally, 166 patients suffering from heart failure with reduced ejection fraction (HFrEF) in two hospitals within the Shaanxi province were included in the present study. These patients were treated according to the Chinese HF guidelines of 2014. Subsequently, these patients were followed up for 50 months, we analyzed the prediction value of baseline Gal-3 to endpoints in these patients. Results: Gal-3 was localized in the cytoplasm and nucleus of cardiomyocytes, often forming aggregates in Mst1-TG mice. Extracellular Gal-3 staining was uncommon in Mst1-TG hearts. However, in β2-AR TG mice, although Gal-3 was also expressed in myocardial cells, it is more highly expressed in interstitial cells (e.g., fibroblasts and macrophages). Plasma Gal-3 was comparable between nTG and Mst1-TG mice, However, plasma Gal-3 was higher in β2-AR TG mice than nTG mice. In HFrEF patients cohort, the median plasma Gal-3 concentration was 158.42 pg/mL. All participants were divided into two groups according to Gal-3 levels. Patients with Gal-3 concentrations above the median were older, had lower plasma hemoglobin, but higher plasma creatinine, tissue inhibitor of metalloproteinases 1 (TIMP-1), left ventricular end systolic diameter (LVESD), left ventricular end-systolic volumes (LVESV) and end-diastolic, and left ventricular end-diastolic volumes (LVEDV) .Spearmen correlation analysis revealed that Gal-3 was positively correlated with TIMP-1 (r=0.396, P<0.001), LVESV (r=0.181, P=0.020) and LVEDV (r=0.190, P=0.015). During a 50-month follow-up, 43 deaths, 97 unplanned re-hospitalizations, and 111 composite endpoint events occurred. Cox analysis demonstrated that although Gal-3 did not provide any prognostic value in either total-HF subjects or coronary-heart-disease (CHD) patients, it did provide prognostic value in non-CHD patients. Conclusion: Although plasma Gal-3 were associated with TIMP-1 and echocardiographic parameters, the diagnostic and prognostic value of Gal-3 in HFrEF depended on the HF etiology.